Changes in Total Acid of Snake fruit (Salacca edulis Reinw.) during Storage Room Temperature - Siska Agustina Dwi Haryanti; Anang Mohamad Legowo; Ahmad Ni'matullah Al-Baarri; Mulyana Hadipernata; Wisnu Broto (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2018)
Snake fruit (Salacca edulis Reinw.) is an indigenous fruit of Indonesia that has weakness as easily-damaged fruit, therefore it has a short shelf life at room temperature. During storage, total acid may be changed in snake fruit. The purpose of this study was to determine the change of total acid in snake fruit during storage at room temperature. The total acid was calculated by titration method using malic acid calculation. Based on the results of the study showed an increase in total acid when snake fruit was stored in room temperature. As conclusion, the total acid was able to be detected in snake fruit during room storage and its change could be determined.